Peran Media “Alphabet Magnetic “ Dalam Pembelajaran Membaca: Studi di SD Kelas Tinggi - Siti Hamidah (LPPM STKIP PGRI Sidoarjo, 2024)
This research aims to describe the role of magnetic alphabet media when learning to read in high school elementary school students. The